Social and sustainable entrepreneurship - Lumpkin, G. T.; Katz, Jerome A. (Advances in entrepreneurship, firm emergence and growth ;, 2011)
This volume considers the timely issues of social and sustainable entrepreneurship. The chapters consider in depth the issues, problems, contexts, and processes that make entrepreneurial enterprises more social and/or sustainable. Top researchers from a diverse set of perspectives have contributed their latest research on a variety of topics such as the role of entrepreneurial bricolage in generating innovations in a social context (Gundry, Kickul, Griffins, Bacq) and emerging themes in social entrepreneurship education (Thiru). Several chapters tackle lingering definitional issues such as the distinctions between social, sustainable, and environmental entrepreneurship (Dean, Sarason, Neenan), or propose social entrepreneurship research agendas based on key research questions found in prior studies (Gras, Mosakowski, Lumpkin). There are brief histories of social change and their entrepreneurial implications (Kucher; Summers), and frameworks for studying different types of social and sustainable entrepreneurship (Lichtenstein). Each of the chapters, in its own way, addresses the progress and promise of social and sustainable entrepreneurship as a future research domain of growing interest and importance.